Socioeconomic determinants and self-rated health among hotel housekeepers in the Balearic Islands (Spain) - Chela-Alvarez, Xenia; Leiva, Alfonso; Bulilete, Oana; Llobera, Joan (Frontiers in Public Health, 2024)
Background: Hotel housekeepers constitute an important occupational group in the Balearic Islands (Spain). Housekeeping is considered low-skilled and precarious and typically involves high physical demands and time pressure. The aim of this study is to analyze the association between the socioeconomic determinants of health and hotel housekeepers’ self-rated health. Methods: This is a cross-sectional study conducted in Primary Health Care in the Balearic Islands (November 2018-February 2019). Hotel housekeepers over 18 years of age with free access to the Balearic Public Health System who had been employed during 2018 were eligible. Results: We enrolled 1,043 hotel housekeepers; the mean score of health perceived status was 72.4/100 (SD 19.0). Those with a lower self-perceived health were statistically significant older, had Spanish nationality, lower level of studies, permanent or recurring seasonal contract, financial difficulties, a higher level of occupational stress, an external locus of control, reported work-life balance difficulties, were former smokers, insufficiently physical active and obese. We found lower scores in self-perceived health status score of -7.159 (CI95% -10.20- -4.12) among hotel housekeepers with osteoarthritis; -6.858 (CI% -11.89- -1.82) among those with chronic depression; -3.697 (CI95% -6.08- -1.31) among those who reported difficulties in work-life balance; -2.414 (CI95% -4.69- -0.13) among participants who performed insufficient physical activity; -2.107 (CI% -4.44- -0.23) among those who reported financial strain. Lower self-rated health was also associated to a higher perceived stress, -1.440 (CI95% -2.09- -0.79); BMI (kg/m2), -0.299 (CI95% -0.53- -0.07); and longer time working as HH -0.177 (CI95% -0.33- -0.03). Conclusions: Our results underscore the importance of psychosocial (such as difficulties in work-life balance and occupational stress) and material factors (such as financial difficulties) when explaining differences in self-perceived health. Public health interventions aimed at improving health status must consider inequalities in material and working conditions.